2015
DOI: 10.12952/journal.elementa.000050
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect photolysis of triclocarban in the presence of dissolved organic matter

Abstract: Photolysis is an important attenuation pathway for the removal of wastewater effluent organic micropollutants from surface waters. In this work, direct and indirect processes leading to the degradation of the disinfectant, triclocarban were studied. Photo-irradiation experiments were conducted in water collected from Old Woman Creek (OWC) a tributary of Lake Erie near Huron, OH, USA and in solutions of fulvic acids isolated from the Suwannee River, Georgia, USA (SRFA), Old Woman Creek (OWCFA) and Pony Lake, An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In addition to adsorption and photocatalysis, some organic contaminants can undergo direct photolysis under light irradiation without photocatalyst, denoted as path 3 in Figure 1. For example, tricholocarbon (TCC), a disinfectant [23], and β-blocker as a pharmaceutical ingredient [24], can be efficiently degraded via direct photolysis under sunlight. In practice, adsorption, photocatalysis, and direct photolysis occur simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to adsorption and photocatalysis, some organic contaminants can undergo direct photolysis under light irradiation without photocatalyst, denoted as path 3 in Figure 1. For example, tricholocarbon (TCC), a disinfectant [23], and β-blocker as a pharmaceutical ingredient [24], can be efficiently degraded via direct photolysis under sunlight. In practice, adsorption, photocatalysis, and direct photolysis occur simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction rate constant for PFOA degradation was reported as 0.0295 min −1 at pH=10, about 49 times higher than that at pH-5. Thus, initial pH conditions increased the concentration of hydrated electrons and supported the reductive mineralization of PFAS in a homogeneous catalytic system [ 92 ]. This section discusses the role of nanocomposites and microparticle-based photocatalysis.…”
Section: Photocatalytic Degradation Of Pfasmentioning
confidence: 99%
“…The photolysis of triclosan (TCS), a similar antimicrobial compound, has been extensively studied because it photodegrades into potentially toxic photoproducts, including chlorophenols and dioxin congeners, TCC has garnered much less attention. Guerard et al and Trouts and Chin reported significant indirect photolysis mediated by dissolved organic matter (DOM), and only one study has identified photochemically derived products (4-chloroaniline, 3,4-dichloroaniline, 4-chlorophenyl isocyanate, and 3,4-dichlorophenyl isocyanate) after photolysis . Nonetheless, to date, there have been no studies that have examined the toxicity of TCC photoproducts on aquatic organisms and only one that we are aware of for triclosan .…”
Section: Introductionmentioning
confidence: 99%